A novel approach for posterior bite collapse in an adult with crossbite anterior using a 3D-printed bite riser - Alhasyimi, Ananto Ali; Indra, Putu; Rosyida, Niswati Fathmah; Retnaningrum, Yanuarti; Setijanto, R. Darmawan; Vázquez-Santos, Francisco José (Dental Journal (Majalah Kedokteran Gigi), 2024)
Background: Managing an adult patient presenting with an anterior crossbite in conjunction with posterior bite collapse (PBC) is a difficult challenge. Purpose: The purpose of this case study is to highlight the accuracy that can be attained with the utilization of a three-dimensional (3D) printed bite riser in the correction of PBC accompanied by an anterior crossbite in an adult patient with Class III malocclusion. Case: A 64-year-old male complained of being unable to chew properly. Extraoral examination revealed a concave profile with a protrusive mandible. The patient exhibits a 5 mm anterior crossbite and has missing lower posterior molars, resulting in bilateral PBC. The cephalometric analysis revealed skeletal Class III patterns (SNA: 82.19o; SNB: 86.34o; ANB: -4.15°), with protrusion and counterclockwise rotation of the mandible (SN-OP: 3.84o). Case Management: By utilizing a 3D-printed bite riser in conjunction with temporary anchoring devices (TADs), it is possible to resolve the issue of an anterior crossbite accompanied by PBC. This is achieved by repositioning the elongated posterior segments on both sides of the maxilla to generate vertical space for mandibular tooth rehabilitation, retracting the anterior segment, and narrowing the lower arch. Simultaneously, the crossbite on both sides was corrected, a Class I and ideal overbite and overjet were achieved, the occlusal vertical dimension increased, the occlusal plane angle was corrected (7.51o), and an acceptable ANB angle (-1.36°) was accomplished. The treatment lasted 18 months and yielded sustained results after a one-year retention period. Conclusion: Integrating 3D printing technology in orthodontic treatment offers numerous options for managing challenging cases such as PBC while also reducing the treatment length. The patient was satisfied with the results achieved.